Language and socioemotional development in early childhood: The role of conversational turns. Issue 5 (6th April 2021) - Gómez, Esteban; Strasser, Katherine
Abstract: This study examines the role of language environment (number of conversational turns) in the development of socioemotional competencies between 18 and 30 months. The language environment of 43 infants and their social‐emotional competencies were measured at 18 months and again at 30 months. Multiple regressions showed a significant contribution of turns at 18 months on socioemotional competencies at 30 months, controlling for their initial levels, child vocalizations, maternal warmth, and social risk. Cross‐lagged analysis revealed that the direction of the longitudinal relation between turns and emotional competencies is more likely to go from turns to socioemotional development than the other way around. Implications for theory and research are discussed.